2014
DOI: 10.1007/s10048-014-0420-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-338-3p is over-expressed in blood, CFS, serum and spinal cord from sporadic amyotrophic lateral sclerosis patients

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive and seriously disabling adult-onset neurological disease. Ninety percent of ALS patients are sporadic cases (sALS) with no clear genetic linkage. Accumulating evidence indicates that various microRNAs (miRNAs), expressed in a spatially and temporally controlled manner in the brain, play a key role in neuronal development. In addition, microRNA dysregulation contributes to some mental disorders and neurodegeneration diseases. In our research, the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 42 publications
2
88
0
1
Order By: Relevance
“…In ALS, several studies have reported the occurrence of miRNAs dysregulation (Waller et al, 2017b; Matamala et al, 2018; Vejux et al, 2018; Vrabec et al, 2018). Among the others, a disease-specific two-fold upregulation of miR-338-3p, involved in apoptosis, neurodegeneration and glutamate clearance, has been reported in blood leukocytes, CSF serum, and spinal cords of patients with sALS compared to controls (De Felice et al, 2014). Furthermore, 30 miRNAs significantly downregulated have been identified in the serum of fALS patients, the majority of them already dysregulated in pre-symptomatic subjects carrying some of the mutations causative of the disease (Freischmidt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In ALS, several studies have reported the occurrence of miRNAs dysregulation (Waller et al, 2017b; Matamala et al, 2018; Vejux et al, 2018; Vrabec et al, 2018). Among the others, a disease-specific two-fold upregulation of miR-338-3p, involved in apoptosis, neurodegeneration and glutamate clearance, has been reported in blood leukocytes, CSF serum, and spinal cords of patients with sALS compared to controls (De Felice et al, 2014). Furthermore, 30 miRNAs significantly downregulated have been identified in the serum of fALS patients, the majority of them already dysregulated in pre-symptomatic subjects carrying some of the mutations causative of the disease (Freischmidt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This was previously demonstrated where several studies have indicated significantly high correlations between blood (serum and plasma) and CSF levels of the same biomarker [34,38,44,118]. However, other studies have also demonstrated that levels of biomarkers, that were discovered in blood, did not correlate with the levels of that same biomarker found in the CSF, suggesting that these 2 fluids are independently regulated [105,117].…”
Section: Biomarkers In Blood (Serum and Plasma)mentioning
confidence: 78%
“…miRNA181a-5p [116], miRNA-143-5p [117], miRNA-574-5p [117], and miRNA-338-3p [118] are the only 4 that have been found to be increased in CSF from patients with ALS. While the physiological roles of most of these miRNAs still remains to be defined within the context of ALS, expression of miRNA-143-5p and miRNA-574-5p was shown to be decreased in lymphoblastoid cell lines (LCL) …”
Section: Micrornamentioning
confidence: 96%
“…miR-206 was upregulated in serum derived from ALS patients as well as in SOD1 G93A mice compared to control mice (Toivonen et al., 2014). In a larger patient cohort, the expression of miR-338-3p was significantly upregulated in the serum of sALS patients, potentially helping in the understanding of sALS pathogenesis and early diagnosis biomarkers (de Felice et al., 2014). Clearly, the role of miRNAs and their potential use as biomarkers in ALS requires further investigation.…”
Section: Introductionmentioning
confidence: 99%